Prevention of lightning related adverse effects: knowledge, attitudes and practices among residents in Kiriella Medical Officer of Health area - Kasunee Kalubowila; Hemantha Herath; Novil Wijesekara (College of Community Physicians of Sri Lanka, 2018)
Background: Lightning is an uncommon but potentially devastating cause of injury in both developed and developing countries. These injuries feature high mortality and significant long-term morbidity, thus prompt preventive and protective measures are essential.   Objective: To describe the knowledge, attitudes and practices on prevention of lightning related adverse effects and associated socio-demographic factors among residents in Kiriella Medical Officer of Health (MOH) area.   Methods: A cross-sectional study was conducted among 510 residents aged 18-64 years and living for a minimum period of one year in Kiriella MOH area. A multi-stage cluster sampling method was used. Data were collected using an interviewer-administered questionnaire on knowledge (score range: 0-21), attitudes (score range: 0-15) and practices (score range: 0-5) on lightning related adverse effects. Odds ratio (OR) was calculated to assess their relationship with socio-demographic factors.   Results: The response rate was 98.4%. There were 301 males (60%). The mean overall knowledge score was 11.8 (SD=1.6) while 12.4% (n=62) scored more than 50% of the total score. Favourable attitudes were reported by 87.5% (n=439) and satisfactory practices by 78.7% (n=395). Good knowledge was significantly associated with younger age (OR=1.8), male sex (OR=4.1), Sinhala ethnicity (OR=5.1) and higher level of education (OR=1.9); and favourable attitudes with younger age (OR=2.0), Sinhala ethnicity (OR=2.1) and higher level of education (OR=1.6).In contrast, satisfactory practices were significantly associated with older age (OR=1.2) and higher level of education (OR=2.1).   Conclusions: Despite having poor knowledge, residents in areas vulnerable to lightning showed favourable attitudes and satisfactory practices. Good knowledge, favourable attitudes and satisfactory practices were determined commonly by the level of education and age. These findings should be considered when targeting them for primary prevention.